Moving toward shared realities through empathy in mathematical modeling: An ecological systems theory approach. (4th March 2020) - Edelen, Daniel; Bush, Sarah B.; Simpson, Heather; Cook, Kristin L.; Abassian, Aline
Abstract: The mathematics education community has routinely called for mathematics tasks to be connected to the real world. However, accomplishing this in ways that are relevant to students' lived experiences can be challenging. Meanwhile, mathematical modeling has gained traction as a way for students to learn mathematics through real‐world connections. In an open problem to the mathematics education community, this paper explores connections between the mathematical modeling and the nature of what is considered relevant to students. The role of empathy is discussed as a proposed component for consideration within mathematical modeling so that students can further relate to real‐world contexts as examined through the lens of Ecological Systems Theory. This is contextualized through a classroom‐tested example entitled "Tiny Homes as a Solution to Homelessness" followed by implications and conclusions as they relate to mathematics education.